"Mr de Bussy" is More Employable than "Mr Bussy": The Impact of a Particle Associated with the Surname of an Applicant in a Job Application Evaluation Context. (3rd April 2017) - Guéguen, Nicolas
Abstract : Previous studies examining the effect of surnames on evaluations have shown that surnames are associated with connotations which influence how we evaluate people. In this experiment, conducted in France, we examined the effect of the nobiliary particle "de" associated with a surname in a job application evaluation situation. A male applicant's résumé was presented to participants, randomly divided into two independent groups, who were asked to evaluate him in relation to a job offer. The offer was for an assistant in human resources in a mid-size company, and the résumé was from a 23-year-old male applicant with a university education in human resources. Depending upon the experimental condition, the applicant's full name was "Julien Bussy" or "Julien de Bussy, " but the résumé was identical in both conditions. Results indicated that the applicant whose surname included a particle was perceived to be more serious, competent, confident, and clever than the applicant without the particle. In the end, the participants in the particle condition believed that the applicant would have more chances of being selected for the job than the applicant without the particle. This effect was particularly noted with female participants. These results thus support the notion that the nobiliary particle attached to an individual's surname has implications for people's evaluation of that person.